2009
DOI: 10.4102/hts.v65i1.124
|View full text |Cite
|
Sign up to set email alerts
|

<i>Hamartia:</i> Foucault and Iran 1978–1979 (1: Introduction and texts)

Abstract: In 1978 Michel Foucault went to Iran as a distinguished intellectual but novice political journalist, controversially reporting on the unfolding revolution, undeniably compromising and wounding his reputation in the European intellectual community. Given the revolution’s bloody aftermath and its violent theocratic development, is Foucault’s Iranian expedition simply to be understood as hamartia, a critical error in judgement, with disastrous consequences for his legacy? What exactly did Foucault hope to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…The research background of this work comprises two elaborate articles that I published in 2009 regarding Foucault's involvement Preface xx in the Iranian revolution (Beukes 2009a(Beukes , 2009b. I found it compulsory to change my position on a number of issues addressed in those articles, in the light of the recent (and crucial) developments in the scholarship (especially with regard to Behrooz Ghamari-Tabrizi's [2016] and Marnia Lazreg's [2017] outstanding works, as well as Iran Namag 3[2], Special Issue on Foucault in Iran, under editorship of Mohamad Tavakoli-Targhi and Ghamari-Tabrizi [2018]).…”
Section: Prefacementioning
confidence: 99%
See 1 more Smart Citation
“…The research background of this work comprises two elaborate articles that I published in 2009 regarding Foucault's involvement Preface xx in the Iranian revolution (Beukes 2009a(Beukes , 2009b. I found it compulsory to change my position on a number of issues addressed in those articles, in the light of the recent (and crucial) developments in the scholarship (especially with regard to Behrooz Ghamari-Tabrizi's [2016] and Marnia Lazreg's [2017] outstanding works, as well as Iran Namag 3[2], Special Issue on Foucault in Iran, under editorship of Mohamad Tavakoli-Targhi and Ghamari-Tabrizi [2018]).…”
Section: Prefacementioning
confidence: 99%
“…Oliver 2010:15-16). This question also provided impetus to Foucault's involvement in Iran from September 1978to April 1979 According to Beukes (2009a), when Foucault went to Tehran in September 1978, he: Foucault thus was an influential thinker, precisely because of his fearless originality: in Discipline and Punish, Foucault (1975) had argued, for instance, that liberal democracy was, in fact, 'a disciplinary society with a ferocious governmentality that punished with less physical severity in order to punish with greater efficiency' (Beukes 2009a:5). Foucault's critical resistance to modernity (Beukes 2009a) suggested that:…”
Section: Prefacementioning
confidence: 99%
“…Until the events of 9/11, the rise of radical Islam had received little attention from the Western liberal tradition, because leftists have always been unsure what to make of the radical kind of anti-imperialism in those radical Islamic structures (far more radical anti-imperialist than the Marxist Left ever was), unsure what to make of its rejection of Western culture whilst the technological advantages of this culture were being retained (as Foucault's reflections on the Iranian army in September 1978 and the 'cassette tape culture' signifies -Beukes 2009), unsure what to make of the unique kind of 'archaic fascism' in its ranks (Rodinson 2005:268), a fascism very far removed from Leftist discourse. Some anti-imperialists, in my mind, were furthering highly suspect culture-critical claims in their interpretations of the events of 9/11: In 2005, I have argued strongly against what I consider to be the glorification of pure and simple terrorism found in the later works of Jean Baudrillard, and in the works of other anti-imperialists such as Paul Virilio and Slavoj Zizek who, in their attempt to find an anti-globalist premise and an 'aestheticsacrificial basis' for the attacks, expressed what I described as a 'morbid, tragic and deeply unphilosophical admiration' for the terrorists (Beukes 2005(Beukes :1111(Beukes , 1114.…”
Section: Introduction: Foucault Scholarship and 9/11mentioning
confidence: 96%
“…Against the backdrop of the introduction, contextualisation and discussion of Foucault's Iran writings in the preceding 1 article, I will, in this second article, attempt to move closer to a nuanced understanding of Foucault's presumed hamartia regarding his involvement in the Iran revolution of 1978-1979, by engaging three recent secondary texts on the basis of the suggestions or preliminary conclusions in the fi rst article (Beukes 2009). I will therefore use those suggestions 2 as implicit premises for the analysis and evaluation of these secondary texts, eventually moving toward a rehabilitation of Foucault's unique philosophical grace, via the notion of an 'ethics of Self-discomfort'.…”
Section: Introduction: Foucault Scholarship and 9/11mentioning
confidence: 98%
“…Foucault was intens bewus van 'n 'epistemologies-anargistiese oorhaastigheid' (Beukes 2005(Beukes :1102kyk Miller 1994:333) by sy Franse tydgenote -veral Derrida -en het hom nie laat verlei om hom die die begrip 'postmodern' te laat welgeval nie, welwetend dat dit spoedig weer as 'n normaliserende, dissiplineringsmatige korset sou begin funksioneer -wat uiteindelik in terme van 'n 'epistemologiese uitbranding van die postmoderne projek' (Beukes 2005(Beukes :1102 Foucault 2.0 (2006), het dit duidelik geword dat die navorsing groter agting behoort te toon vir die ontwikkeling in Foucault se oeuvre, in terme van drie aanduibare fases (Paras 2006:5-18): Die eerste fase in Foucault se werk was grootliks gemoeid met die filosofiesteoretiese grondslae van die psigiatrie in die laat 1950's, sowel as sy deelname aan die laat-eksistensialistiese, vroegstrukturalistiese debat in Frankryk in die eerste jare van die 1960van die 's (vgl. Paras 2006 (Beukes 2009a(Beukes , 2009b) en die publikasies wat daaruit voortgekom het. Dit sluit ook in die uiteindelike publikasie van sy lesings by die Collège de France vanaf die vroeg 1980's, wat ook die wesenlike inhoud van sy lesings by Buffalo en Berkeley in die VSA (kyk Foucault 1971:72-73) tot net voor sy afsterwe in 1984 bepaal het, en wat uiteindelik behoorlik gesistematiseer, getematiseer en gekommentarieer is deur Paras (2006).…”
unclassified